The influence of the existence of new landmark on urban spatial - Sari, Suzanna Ratih; Indrosaptono, Djoko; Hilmy, Muhammad Fariz (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
The Old City Museum, located in the middle of the Bubakan Roundabout, is one of the new landmarks in Semarang City due to its magnificent existence and attractive architectural design. However, the existence of this museum has changed the urban spatial in the area, such as flow of vehicles around the museum, making it difficult for people to access detours because the area is no longer in the form of a roundabout, and also the unavailability of special parking spaces for this museum makes visitors forced to park on the shoulder of the road or in the shophouses around the roundabout. Therefore, in accordance with this phenomenon, this study aims to determine the significant existence of this museum to the spatial layout in the Bubakan area, Semarang, seen from the eight of urban design elements. The qualitative method was used to find answers to phenomena and problems in the field. Observation and interview with tourists and local people were conducted to get the information related the effectiveness of urban spatial in Bubakan Area, Semarang. The result showed the importance of the existence of this museum and provided suggestions to make it more conducive.